2022
DOI: 10.1063/5.0085368
|View full text |Cite
|
Sign up to set email alerts
|

Study on bandgap of a novel phononic crystal with low-frequency sound insulation

Abstract: To solve the problem of low-frequency noise in the environment, a two-dimensional Helmholtz-type phononic crystal with a labyrinth tube was designed in the paper. First, the low-frequency band structure was calculated by the finite element method (FEM) and transfer matrix method (TMM). Second, the bandgap formation was analyzed by using an acoustic pressure field, and the “spring-oscillator” equivalent model of the structure was established. Finally, the influences of structural parameters on the first bandgap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Subpopulations are then subjected to constraint determination and ideal point finding operations. (7) The parent and child populations are merged, and sequential operations, including non-dominated sorting, target space normalization, a calculation of reference lines, an association of individuals with reference points, and a selection of dominant populations are carried out. (8) If the termination condition is met, the optimal Pareto solution is output; otherwise, steps ( 5) through ( 8) are repeated.…”
Section: Joint Parallel Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subpopulations are then subjected to constraint determination and ideal point finding operations. (7) The parent and child populations are merged, and sequential operations, including non-dominated sorting, target space normalization, a calculation of reference lines, an association of individuals with reference points, and a selection of dominant populations are carried out. (8) If the termination condition is met, the optimal Pareto solution is output; otherwise, steps ( 5) through ( 8) are repeated.…”
Section: Joint Parallel Simulation Methodsmentioning
confidence: 99%
“…Using parameters, such as the total stiffness and damping, as independent variables, and the average sound absorption coefficient in a specific frequency band as the optimization objective, Li et al [6] have created a type of loudspeaker with a good sound absorption performance. Han et al [7] have constructed a labyrinthine Helmholtz phonon crystal and have concluded that increasing the tube length and preserving a small lattice constant could significantly enhance the structure's low-frequency sound insulation capacity. Chen et al [8] have constructed a resonant metamaterial plate with a front radial film and have concluded that increasing the plate thickness and decreasing the film thickness could effectively improve the broadband and low-frequency properties.…”
Section: Introductionmentioning
confidence: 99%